Muon reconstruction performance and constraints on off-shell Higgs Boson production and the Higgs Boson total width with the ATLAS detector and charm production at low transverse momentum with the CDF detector - Marchese, L (2019)
The latest constraints on the signal strength of the off-shell Higgs boson production and the Higgs boson total width in the ZZ → 𝓁𝓁νν final state are presented. The Higgs boson is studied in decays to a pair of on-shell Z bosons where one of the two Z bosons decays to a pair of leptons - 𝓁 stands for either an electron or a muon - and the other to a pair of neutrinos. The analysis is based on proton-proton collision data collected by the ATLAS detector in 2015 and 2016 at a centre-of-mass energy of 13 TeV at the Large Hadron Collider (LHC), corresponding to a total integrated luminosity of 36.1 fb−1. An observed (expected) upper limit on the off-shell Higgs signal strength, defined as the event yield normalised to the Standard Model prediction, of 5.3 (4.4) is obtained at 95% confidence level (CL) in the ZZ → 𝓁𝓁νν channel. After the combination with similar results from the ZZ → 4𝓁 channel the reported observed (expected) limit is 3.8 (3.4) at 95% CL. Assuming the ratio of the Higgs boson couplings to the Standard Model predictions is independent of the momentum transfer of the Higgs production mechanism considered in the analysis, a combination with the on-shell signal-strength measurements yields an observed (expected) 95% CL upper limit on the Higgs boson total width of 14.4 (15.2) MeV.